Salafi Ulama in UMNO: political convergence or expediency? - Osman, Mohamed Nawab (Contemporary Southeast Asia, 2014)
The Salafi ulama (religious scholars) in Malaysia have seen their religious and political influence amplified over the last five years. Operating within a newly formed organization, the Pertubuhan Ilmuwan Malaysia (ILMU) and the newly augmented United Malays National Organization's (UMNO) young ulama wing, Salafi scholars play a key role in providing Islamic legitimacy to the government and defending it against the opposition Islamist party, the Pan-Malaysian Islamic. - Party (PAS). The decision by Salafi scholars to support the Malaysian government is striking given their hardline views on the implementation of Islamic laws and their opposition to democracy. This paper seeks to understand the reasons for the Salafi ulama's support for UMNO. It argues that the Salafi ulama's involvement in UMNO is due to a convergence of interest between the two groups and as part of a strategy by the Salafi ulama to expand their influence at both the state and societal levels. The paper examines the religious-political positions of the Salafi ulama on issues such as the Islamic state, the implementation of Islamic laws and democratic political system, and argues that they are opposed to the current state of religious affairs and the political structure of the Malaysian state. Nevertheless, the ulama are working within UMNO to change the political system. For UMNO leaders, the Salafi ulama form an important group that could defend the party against religious attacks from PAS and provide the party with greater religious credence. (Contemp Southeast Asia/GIGA)